2020
DOI: 10.28982/josam.812409
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting mortality in trauma patients hospitalized in the intensive care unit

Abstract: All procedures in this study involving human participants were performed in accordance with the 1964 Helsinki Declaration and its later amendments. Etik Kurul Onayı: Çalışma Harran Üniversitesi etik komitesi tarafından onaylandı (Onay No: E.7334, Tarih: 11 Şubat 2020). İnsan katılımcıların katıldığı çalışmalardaki tüm prosedürler, 1964 Helsinki Deklarasyonu ve daha sonra yapılan değişiklikler uyarınca gerçekleştirilmiştir.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…In another study, it was observed that 50% and 72.2% of patients with APACHE II scores of ≥15 and ≥20, respectively, did not survive [23]. It is noteworthy that mortality increases significantly in patients with APACHE II scores between 21-25 [24,25]. In our study, as the APACHE II score increased, so did mortality significantly, and the APACHE II score was significantly higher among non-survivors.…”
Section: Discussionsupporting
confidence: 50%
“…In another study, it was observed that 50% and 72.2% of patients with APACHE II scores of ≥15 and ≥20, respectively, did not survive [23]. It is noteworthy that mortality increases significantly in patients with APACHE II scores between 21-25 [24,25]. In our study, as the APACHE II score increased, so did mortality significantly, and the APACHE II score was significantly higher among non-survivors.…”
Section: Discussionsupporting
confidence: 50%
“…The intensive care unit (ICU) is a special treatment unit equipped with high technology for rapid intervention, where patients with life-threatening organ failure and who need to be kept under constant observation are followed up and treated [1]. With the increase in the aging population, the increase in the demand for intensive care beds and the high cost of intensive care treatments require careful selection of patients who will benefit from hospitalization in the ICU [2]. Calculation of expected mortality rates of intensive care patients is important in terms of rapid identification of critical patients requiring urgent diagnosis and treatment, standardization of intensive care units, and evaluation and provision of service quality.…”
Section: Introductionmentioning
confidence: 99%